Discretionary Policy (Freies Ermessen) of State Administrative Bodies or Officials in Government Administrative Law - Abdul Latif; Hery Chariansyah (Journal of Social Research, 2024)
The aim is to examine and analyze how state government administrative agencies or officials carry out actions that are in accordance or not in accordance with the Ermessen freies legal conception itself which is known in scientific literature, especially state administrative law. In this case, the term "vrij inititiet" is used by Logeman in his book Eet Staaterecht van Indonesie, while Donner has the term "Vrijheid vanhet bestuur". The object of discussion in literature and practice is the application of discretionary policies or the use of Ermessen freies in order to achieve general welfare. The results of this research found that the meaning of freis Ermessen is the same or in accordance with practice through field research or cases that have occurred and to what extent the regulations that require Ermessen are in accordance with the facts implemented in practice.